The Effect of Music in Reducing Patient's Anxiety Towards Dental Treatment - Ahmad Dzulfikar Samsuddin; Azlan Jaafar; Nurul Huda Mohd Anas; Nur Farhanim Abdol Sukor (Academic Inspired Network, 2024)
Non-Indexed Publication